2010
DOI: 10.1038/aps.2010.40
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium lithospermate B dilates mesenteric arteries by activating BKCa currents and contracts arteries by inhibiting KV currents

Abstract: Aim: To examine the involvement of K + channels and endothelium in the vascular effects of magnesium lithospermate B (MLB), a hydrophilic active component of Salviae miltiorrhiza Radix. Methods: Isolated rat mesenteric artery rings were employed to investigate the effects of MLB on KCl-or norepinephrine-induced contractions. Conventional whole-cell patch-clamp technique was used to study the effects of MLB on K + currents in single isolated mesenteric artery myocytes. Results: MLB produced a concentration-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…MLB was also shown to reduce the expression of VCAM-1 and ICAM-1 to protect endothelial function [22]. Another study confirmed that MLB could promote arterial vasodilation through the activation of BKCa channel of smooth muscle cells [23]. In the present study, we reported a novel pharmacological effect of MLB that could ameliorate microcirculation dysfunction mainly through endothelial-dependent vasodilation and NO release Fig.…”
Section: Discussionsupporting
confidence: 67%
“…MLB was also shown to reduce the expression of VCAM-1 and ICAM-1 to protect endothelial function [22]. Another study confirmed that MLB could promote arterial vasodilation through the activation of BKCa channel of smooth muscle cells [23]. In the present study, we reported a novel pharmacological effect of MLB that could ameliorate microcirculation dysfunction mainly through endothelial-dependent vasodilation and NO release Fig.…”
Section: Discussionsupporting
confidence: 67%
“…There are at least two experiments about SalB acting on the BK Ca channel. One experiment confirmed MLB can make arterial vasodilating through the activation of BK Ca channel (big-conductance Ca 2+ -activated K + channels) of smooth muscle cell and the increase of endothelial NO release [54]. Another one verified that salvianolic acid B could activate the opening of the BK Ca channels of the porcine coronary artery smooth muscle cells.…”
Section: Cardiovascular Pharmacologymentioning
confidence: 99%
“…Danhong injection is a compound preparation extracted from salvia miltiorrhiza and safflower [2] . Compared with conventional traditional Chinese medicine, traditional Chinese medicine injection has the advantages of fast and explicit effect.…”
Section: Discussionmentioning
confidence: 99%